Kerjasama Antarsektor dalam Penanggulangan Banjir dan Partisipasi Warga di Dadok Tunggul Hitam - Aina Ilzahra; Dafina Permata Dasti; Dinda Azzahra Putri; Boni Saputra (CV. ITTC INDONESIA, 2026)
Flooding is a perennial environmental and spatial problem in Dadok Tunggul Hitam Village, Padang City, triggered by high rainfall, low topography, and poor drainage. The complexity of this problem cannot be resolved by the government alone but requires multi-stakeholder collaboration, which has not yet been optimally implemented. This study aims to analyze the effectiveness of intersectoral collaboration and assess local community participation through the Disaster Preparedness Village (KSB) Program in flood preparedness. The research method used is descriptive qualitative. Data were collected through field observations in five affected neighborhood units (RW) (Parak Jambu, Maransi, DPR Ujung, Rawang, and Anyelir Ujung) and in-depth interviews with KSB village and sub-district administrators. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions based on theme grouping (thematic analysis). The results show that community involvement is at a moderate level (65% actively involved), which is influenced by minimal disaster education and limited budget allocation. Nevertheless, this intersectoral collaboration has successfully promoted inclusive decision-making mechanisms through deliberation, accurate validation of victim data, the establishment of a responsive early warning system, and the strengthening of collective community resilience at the grassroots level.